2019
DOI: 10.1093/nar/gkz1058
|View full text |Cite
|
Sign up to set email alerts
|

Single molecule analysis of effects of non-canonical guide RNAs and specificity-enhancing mutations on Cas9-induced DNA unwinding

Abstract: Cas9 has made a wide range of genomic manipulation possible. However, its specificity continues to be a challenge. Non-canonical gRNAs and new engineered variants of Cas9 have been developed to improve specificity, but at the cost of the on-target activity. DNA unwinding is a checkpoint before cleavage by Cas9, and was shown to be made more sensitive to sequence mismatches by specificity-enhancing mutations in engineered Cas9s. Here we performed single-molecule FRET-based DNA unwinding experiments using variou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 37 publications
5
38
0
Order By: Relevance
“…It may be that the effect seen here is unique to the RP hairpin and that empirical design can be used to select for RNA structures that have the desired effect and to avoid unwanted ones. There may also be protospacer specific effects, as observed for the short 5′ modifications (13). The unusual activity of 5′ RP gRNA could be exploited to form stable R-loops without activating DNA cleavage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It may be that the effect seen here is unique to the RP hairpin and that empirical design can be used to select for RNA structures that have the desired effect and to avoid unwanted ones. There may also be protospacer specific effects, as observed for the short 5′ modifications (13). The unusual activity of 5′ RP gRNA could be exploited to form stable R-loops without activating DNA cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…In their recent study, Okafor et al suggested that effects of unpaired 5′ nucleotides can be sequence context specific (13). To explore this, we targeted an alternative protospacer sequence on pSP1, where the 20th nucleotide on the protospacer DNA targeted strand is a cytosine that can base pair with a terminal 5′ guanine on the gRNA spacer ( Figure 3A).…”
Section: ′ Unpaired Nucleotides In Streptococcus Pyogenes Cas9 Grna mentioning
confidence: 99%
See 3 more Smart Citations